MIMO MC-CDMA communications for future cellular systems. - Juntti, Markku (IEEE Communications magazine)
We propose an efficient multiple-input multiple-output concept based on space-time turbo coded modulation and layered spatial multiplexing architectures for cellular multicarrier code-division multiple access systems. We design appropriate receiver algorithms, and compare their performance to competing schemes in a single-cell system. We then evaluate the performance of the scheme in a seven-cell system with universal frequency reuse. The proposed MIMO scheme improves throughput significantly compared to the corresponding single-antenna communications even in the presence of spatial correlation.